EXPERIMENTAL, THEORETICAL AND NUMERICAL INVESTIGATION OF CREEP CHARACTERISTICS OF FISH SCALE POWDER-CHICKEN FEATHER FILLED POLYESTER COMPOSITES - Battawi, Ali; Abed, Balsam (Journal of Applied Engineering Science, 2022)
Natural fibres would play a significant part in the production of composite materials since these fibres are entirely renewable, environmentally friendly, have a high specific strength, inexpensive, and biodegradable. The objective of this research is to investigate the potential of fish scale powder and chicken feather as reinforcing agents in polyester composites, as well as the composites' creep behaviour. Hand lay-up procedures were used to prepare weight fractions (0.2, 0.5, 0.8, and 1.1%) of chicken feather along with 5% fish scale powder. It is observed that the composite with 0.8% chicken feather and 5% fish scale powder showed encouraging results as it enhanced the creep strain by 74.29% and diminished the stress by 40.71% compared with neat polyester. The experimental, theoretical, and numerical results were compared. Good accuracy has been observed, with a relative error of no more than 3.2%. These findings indicate that natural fibres have enhanced creep properties and might be a feasible alternative to industrial applications.
Keywords: polyester composite, Fish scale powder, chicken feather, Burgers model, Prony Series, creepbehaviour